Gradient invariance of slow energy descent: spectral renormalization and energy landscape techniques. (21st October 2020) - Cakir, Hayriye Guckir; Promislow, Keith
Abstract: For gradient flows of energies, both spectral renormalization (SRN) and energy landscape (EL) techniques have been used to establish slow motion of orbits near low-energy manifold. We show that both methods are applicable to flows induced by families of gradients and compare the scope and specificity of the results. The SRN techniques capture the flow in a thinner neighbourhood of the manifold, affording a leading order representation of the slow flow via as projection of the flow onto the tangent plane of the manifold. The SRN approach requires a spectral gap in the linearization of the full gradient flow about the points on the low-energy manifold. We provide conditions on the choice of gradient under which the spectral gap is preserved, and show that up to reparameterization the slow flow is invariant under these choices of gradients. The EL methods estimate the magnitude of the slow flow, but cannot capture its leading order form. However the EL only requires normal coercivity for the second variation of the energy, and does not require spectral conditions on the linearization of the full flow. It thus applies to a much larger class of gradients of a given energy. We develop conditions under which the assumptions of the SRN method imply the applicability of the EL method, and identify a large family of gradients for which the EL methods apply. In particular we apply both approaches to derive the interaction of multi-pulse solutions within the 1 + 1D functionalized Cahn–Hilliard gradient flow, deriving gradient invariance for a class of gradients arising from powers of a homogeneous differential operator.